Affectionate Interactions of Cats with Children Having Autism Spectrum Disorder - Hart, Lynette A.; Thigpen, Abigail P.; Willits, Neil H.; Lyons, Leslie A.; Hertz-Picciotto, Irva; Hart, Benjamin L. (Frontiers in Veterinary Science, 2018)
Mental and physical benefits of dogs have been reported for adults and children with special needs, but less is known about benefits of cats for children. A cat that can be held by a child could provide important therapeutic companionship for children with mild or severe autism spectrum disorder (ASD) who otherwise may lack prosocial behaviors. Because relatively little is known about the behavior of cats around children, we conducted this study in two phases. Phase 1 gathered web-survey data from families having an adult cat and a child with ASD (n = 64). In Phase 2, there were direct telephone interviews of parents having a child with ASD (n=16), less affected ASD (n=6), and typical development (n=13). From the Phase 1 web survey of families with ASD children, affectionate interactions of the cats with children were common. Most parents with ASD children volunteered positive comments regarding the cat, such as characterizing the cat as calming to the child, a soothing protector or a guardian. In the interviews in Phase 2, most parents with ASD children characterized cats as at least moderately affectionate to the child. However, cats with ASD children were reported to exhibit less affection than those with typically developing children or children less affected with ASD. Most cats in both the web survey and interviews were affectionate and supportive of the specified children, whether with ASD or typically developing, and aggression by cats was infrequent. ASD children valued the relationship with the cat at high levels, similar to typically developing children, pointing to the importance and potential usefulness of selecting affectionate and compatible cats for ASD children.